Human resource practices and employees' intention to stay in the Kuala Lumpur hotel industry / Dr. Hazrina Ghazali ... [et al.] - Ghazali, Hazrina; Mohd Nasyuki, Nasyira; Oon, Xiao Yi; Ishak, Maisarah (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The main purpose of this study was to examine the relationship of human resource practices and employees' intention to stay in the KL hotel industry. Seven human resource practices; namely recruitment and selection, training, the compensation system, performance appraisal, job security, employee empowerment, and communication were used as variables to predict such intention. A total of 340 questionnaires were distributed to employees who were currently working in two, three and four stars rating hotels. Data were analyzed by using SPSS and results indicated that all practices have significant positive relationships with employees' intention to stay. It was also found that practices that are commonly being carried out in the KL hotel industry were communication, training, recruitment and selection, teamwork, and performance appraisal. It is hoped that the findings of this study will help hotel managers to implement these practices so that their employees remain working with them and maximize the employees' intention to stay.